2019
DOI: 10.1137/18m1191373
|View full text |Cite
|
Sign up to set email alerts
|

Local Fourier Analysis of Balancing Domain Decomposition By Constraints Algorithms

Abstract: Local Fourier analysis is a commonly used tool for the analysis of multigrid and other multilevel algorithms, providing both insight into observed convergence rates and predictive analysis of the performance of many algorithms. In this paper, for the first time, we adapt local Fourier analysis to examine variants of two-and three-level balancing domain decomposition by constraints (BDDC) algorithms, to better understand the eigenvalue distributions and condition number bounds on these preconditioned operators.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Similar work has been done for several other common coupled systems, such as poroelasticity [12,28,30] or Stokes-Darcy flow [29]. With insights gained from this and similar work, LFA has also been applied in much broader settings, such as the optimization of algorithmic parameters in balancing domain decomposition by constraints preconditioners [5]. While the use of a Fourier ansatz inherently limits LFA to a class of homogeneous (or periodic [1,23]) discretized operators (block-structured with (multilevel) Toeplitz blocks), recent work has shown that LFA can be applied to increasingly complex and challenging classes of both problems and solution algorithms, limited only by one's ability to optimize parameters within the LFA symbols.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Similar work has been done for several other common coupled systems, such as poroelasticity [12,28,30] or Stokes-Darcy flow [29]. With insights gained from this and similar work, LFA has also been applied in much broader settings, such as the optimization of algorithmic parameters in balancing domain decomposition by constraints preconditioners [5]. While the use of a Fourier ansatz inherently limits LFA to a class of homogeneous (or periodic [1,23]) discretized operators (block-structured with (multilevel) Toeplitz blocks), recent work has shown that LFA can be applied to increasingly complex and challenging classes of both problems and solution algorithms, limited only by one's ability to optimize parameters within the LFA symbols.…”
mentioning
confidence: 80%
“…Generalizations of (2.6) are also possible, such as to minimize the condition number of a preconditioned system corresponding to other solution approaches. For example, the authors of [5] use LFA to study the condition numbers of the preconditioned system in one type of domain decomposition method, where a different minimax problem arises. Similarly, in [43], the optimization of E(p, θ) is considered in the highly non-normal case.…”
Section: Minimax Problem In Lfamentioning
confidence: 99%
“…. By using macro-elements, [21,9], our LFA of p-multigrid can be extended to LFA of h-multigrid. For 1D analysis, a macro-element is single element comprising of a pair of sub-elements with separate quadrature spaces, which is equivalent to partially assembling the finite element operator on two element subdomains.…”
Section: Extension To H-multigridmentioning
confidence: 99%
“…Although [31] discussed LFA of p-multigrid for the discontinuous Galerkin method, this formulation cannot be extended to the continuous Galerkin method. Our LFA formulation for p-multigrid with high-order finite element discretizations for the continuous Galerkin method can be generalized to reproduce previous work on h-multigrid for high-order finite elements [16] and can be extended to LFA for hmultigrid of finite difference discretizations that can be represented via finite element discretizations as well as LFA of block smoothers [22,9] We investigate the performance of Jacobi and Chebyshev semi-iterative smoothers for p-multigrid with aggressive coarsening for the scalar Laplacian in one and two dimensions, and we validate our LFA of p-multigrid with the scalar Laplacian in three dimensions against numerical experiments. Our analysis demonstrates that the performance of p-multigrid with these two smoothers degrades as we coarsen more aggressively.…”
mentioning
confidence: 99%
“…On the other hand, LFA could also be applied to different types of discretization schemes as well, including the continuous Galerkin finite‐element, 2,15 the discontinuous Galerkin, 16,17 the finite‐difference, 18,19 and the finite‐volume methods 20 . Recently, LFA has been designed to combine with/improve the periodic stencil operator, 21 the domain decomposition method, 22 and multicolored contexts 23,24 …”
Section: Introductionmentioning
confidence: 99%